2007
DOI: 10.1186/1471-2164-8-303
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of chickpea genes differentially regulated in response to high-salinity, cold and drought

Abstract: Background: Cultivated chickpea (Cicer arietinum) has a narrow genetic base making it difficult for breeders to produce new elite cultivars with durable resistance to major biotic and abiotic stresses. As an alternative to genome mapping, microarrays have recently been applied in crop species to identify and assess the function of putative genes thought to be involved in plant abiotic stress and defence responses. In the present study, a cDNA microarray approach was taken in order to determine if the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(110 citation statements)
references
References 62 publications
4
98
0
3
Order By: Relevance
“…Many studies reported several genes or ESTs to be involved in various stress responses based on transcriptomic and proteomic studies (Pandey et al 2006(Pandey et al , 2008Mantri et al 2007;Molina et al 2008Molina et al , 2011Varshney et al 2009a). However, gene discovery has been very limited in chickpea.…”
Section: Transcriptome Sequencing In Chickpeamentioning
confidence: 99%
“…Many studies reported several genes or ESTs to be involved in various stress responses based on transcriptomic and proteomic studies (Pandey et al 2006(Pandey et al , 2008Mantri et al 2007;Molina et al 2008Molina et al , 2011Varshney et al 2009a). However, gene discovery has been very limited in chickpea.…”
Section: Transcriptome Sequencing In Chickpeamentioning
confidence: 99%
“…These include developmentrelated ARPs such as the fruit repression SAR5 from strawberry [21], the dormancy-associated SbDRM1 from sorghum and pea [22] [23], a germination-related gene from tobacco [24], a hypocotyl elongation-related RpARP from black locust [25], the auxin-induced EuNOD-ARP1 gene from Elaeagnus umbellate root nodules [26], and the cucumber CsGRP1, which accumulates on the upper L. M. Wu et al side of seedlings during gravimorphogenesis [27]. Stress-responsive ARPs include the drought/heat-induced AtARP1 from Arabidopsis [28], a gene induced by salinity and cold from hot pepper [29], five genes responsive to drought/ cold/high-salinity from chickpea [30], the salinity/drought-responsive BnARP from B. napus [31], and two genes responsive to chilling, heat shock and salt stress (BrARP1 and BrDRM1) from B. rapa [32]. However, the role of ARPs that mediate resistance or susceptibility to insects and fungi is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…La aparición de métodos de alta capacidad para estudiar la expresión génica está permitiendo identificar un gran número y variedad de genes regulados por las bajas temperaturas, algunos de estos, con una posible función reguladora y muchos todavía con una función desconocida (Seki et al, 2001;Kreps et al, 2002;Maruyama et al, 2004;Vogel et al, 2005;Lee et al, 2005;Cheng et al, 2007;Mantri et al, 2007;Kilian et al, 2007;Usadel et al, 2008;Maul et al, 2008;Fernandez et al, 2008;. La aclimatación al frío está correlacionada con la activación de numerosos genes de repuesta a bajas temperaturas (Fowler y Thomashow, 2002).…”
Section: Mecanismos Moleculares De Tolerancia Al Fríounclassified
“…La disponibilidad de numerosas colecciones de cDNA ha permitido la construcción de micromatrices para un gran número de especies vegetales, muchas de ellas con un alto interés agronómico, como arroz (Rabbani et al, 2003;Lian et al, 2006), maíz , soja (Vodkin et al, 2004;Ainsworth et al, 2006), patata (Stupar et al, 2007), tomate (Alba et al, 2005), fresa (Aharoni et al, 2004), trigo (Gulick et al, 2005), garbanzo (Mantri et al, 2007), girasol (Fernández et al, 2008), melocotón (Ogundiwin et al, 2008), y cítricos (Forment et al, 2005, Martinez-Godoy et al, 2008.…”
Section: Análisis Del Transcriptoma Del Flavedo En Respuesta Al Frío unclassified
See 1 more Smart Citation